2012
DOI: 10.1016/j.socscimed.2012.05.017
|View full text |Cite
|
Sign up to set email alerts
|

A life course model of self-rated health through adolescence and young adulthood

Abstract: This paper proposes and tests a life course model of self-rated health (SRH) extending from late childhood to young adulthood, drawing on three waves of panel data from the U.S. National Longitudinal Study of Adolescent Health (Add Health). Very little research has examined SRH during the early decades, or whether and how these self-assessments reflect experiences in the family of origin. Background characteristics (parental education, income, and family structure), parental health conditions (asthma, diabetes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
98
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 52 publications
(61 reference statements)
4
98
0
4
Order By: Relevance
“…Few papers 12,13 have analysed SRH trends across time, but mainly in single countries; whereas the HBSC dataset allows for a very wide comparison of trends among almost all European countries over a 10 year cycle, a period where many important changes have taken place in Europe as well as around the world. For this reason, the underlying assumption of our study is that change in adolescent self-rated health across the last decade might be, at least partially, influenced by macro socio-economic conditions during this period.…”
Section: Introductionmentioning
confidence: 99%
“…Few papers 12,13 have analysed SRH trends across time, but mainly in single countries; whereas the HBSC dataset allows for a very wide comparison of trends among almost all European countries over a 10 year cycle, a period where many important changes have taken place in Europe as well as around the world. For this reason, the underlying assumption of our study is that change in adolescent self-rated health across the last decade might be, at least partially, influenced by macro socio-economic conditions during this period.…”
Section: Introductionmentioning
confidence: 99%
“…1,3,[14][15][16][17][18][19][20][21][22][23][24] Factors comorbid with adolescent smoking and ND, including substance use (alcohol, marijuana) and mental health problems (depression, anxiety, disruptive disorders), predict poor health in young adulthood. [15][16][17][18]20,[25][26][27][28][29] Parents can affect offspring health through genetic factors, physical and mental health, health behaviors, and socioeconomic status. 18,[30][31][32][33][34][35] Studies have found that parental health conditions directly predict poorer self-rated health in young adult offspring, and indirectly through offspring's health behaviors.…”
Section: Nicotine Dependence In Adolescence and Physical Health Symptmentioning
confidence: 99%
“…[15][16][17][18]20,[25][26][27][28][29] Parents can affect offspring health through genetic factors, physical and mental health, health behaviors, and socioeconomic status. 18,[30][31][32][33][34][35] Studies have found that parental health conditions directly predict poorer self-rated health in young adult offspring, and indirectly through offspring's health behaviors. 18 Parental depression is associated with offspring health problems, such as respiratory illness in childhood, 31 physical symptoms in adolescence, 32 and chronic physical conditions, particularly cardiovascular illness, in mid-adulthood.…”
Section: Nicotine Dependence In Adolescence and Physical Health Symptmentioning
confidence: 99%
See 2 more Smart Citations